CONSUMER PERCEPTIONS OF TRANSACTION SECURITY IN DIGITAL MARKETING ON MARKETPLACE PLATFORMS - Ayu Teresia Hutauruk; Mei Veronika Sri Endang Siagian; Lamtiur Lidia Gultom (Adisam Publisher, 2025)
This study aims to examine consumer perceptions of transaction security in the context of digital marketing on marketplace platforms. Amid the rapid growth of e-commerce and the use of digital marketplaces such as Tokopedia, Shopee, and Bukalapak, the issue of transaction security is one of the key factors influencing consumer purchasing decisions. This study uses a systematic literature review method by analyzing various secondary sources such as scientific journals, articles, and research reports published between 2015 and 2024. The results of the study show that consumer perceptions of security are influenced by various factors, including personal experience, digital literacy, age, and the effectiveness of communication from the platform regarding transaction protection. Marketplaces that provide transparent security systems, buyer protection features, and responsive customer service tend to get positive perceptions from consumers. This finding confirms that perceptions of security not only have an impact on trust, but also have direct implications for purchasing decisions and consumer loyalty. Therefore, transaction security must be a strategic priority in the development of digital services by marketplace platforms.